2007
DOI: 10.1117/12.708204
|View full text |Cite
|
Sign up to set email alerts
|

Data mining learning bootstrap through semantic thumbnail analysis

Abstract: The rapid increase of technological innovations in the mobile phone industry induces the research community to develop new and advanced systems to optimize services offered by mobile phones operators (telcos) to maximize their effectiveness and improve their business. Data mining algorithms can run over data produced by mobile phones usage (e.g. image, video, text and logs files) to discover user's preferences and predict the most likely (to be purchased) offer for each individual customer. One of the main cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In that paper we showed that the combination of such simple color and text-related features performs better than when each type of feature is considered in isolation. Differently from [8] we propose here to capture the visual content of each offer's image as a whole entity through a holistic representation involving Textons [9][10][11][12]. Experiments presented in Section 5.3 show that a Textons-based representation achieves better results when compared against the representation used in [8].…”
Section: The Present Work: Overview Aims and Contributionsmentioning
confidence: 99%
See 4 more Smart Citations
“…In that paper we showed that the combination of such simple color and text-related features performs better than when each type of feature is considered in isolation. Differently from [8] we propose here to capture the visual content of each offer's image as a whole entity through a holistic representation involving Textons [9][10][11][12]. Experiments presented in Section 5.3 show that a Textons-based representation achieves better results when compared against the representation used in [8].…”
Section: The Present Work: Overview Aims and Contributionsmentioning
confidence: 99%
“…Differently from [8] we propose here to capture the visual content of each offer's image as a whole entity through a holistic representation involving Textons [9][10][11][12]. Experiments presented in Section 5.3 show that a Textons-based representation achieves better results when compared against the representation used in [8]. In this paper the Textons-based representation of visual content for each MMS has been used together with text features for learning purpose.…”
Section: The Present Work: Overview Aims and Contributionsmentioning
confidence: 99%
See 3 more Smart Citations